Public policies for the training of public school principals in Brazil: An analysis of the National Program of Basic Education Managers (PNEGEB) - Sottani, Natália Bazoti Brito; Mariano, Sandra Regina Holanda; Moraes, Joysi; Dias, Bruno Francisco (Education Policy Analysis Archives, 2018)
This paper informs the results of the analysis about public policy of training public school principals, implemented through the National Program of Basic Education Managers (PNEGEB), which was in force in Brazil from 2006 to 2016 and was invested the amount of R$70.017.228,06. The analysis was carried out using the perspective of the public policy cycle model (Howlett & Ramesh, 1995, 2003). In-depth interviews were conducted with specialists from the Ministry of Education (MEC), the State Secretariat for Education of Rio de Janeiro and universities participating in the Program, and documents provided by the MEC were consulted. Of the 36,443 vacancies offered, at the end of 2016, only 19,257 principals (53%) had completed the course. The complexity of implementing the Program at the national level and the lack of articulation between the various actors involved in this policy, to a certain extent, explain the high level of evasion. MEC did not evaluate the Program, reaffirming the country's difficulty in evaluating public policies in a consistent manner and enabling it to guide future actions and investments. The discontinuity of the Program and the lack of a public policy to replace it suggest a reduction of this theme among the priorities of the country.